Pengaruh Word Of Mouth Terhadap Keputusan Pembelian Produk Natasha Skin Care Jakarta Pusat - Susanti, Inggit Dessy; Waru, A. Putri Djohar Tenri; Janah, Yunita (Jurnal Administrasi Bisnis, 2023)
Beauty clinics are one type of beauty industry business opportunity that is loved by people today. There are many types of treatments and skincare offered by various beauty clinics. More references cause caution in determining the skincare to be used so that before making a decision, potential customers tend to carry out the process of finding information and filtration. The process of finding information can be done by looking at reviews either from online stores or seeing trusted beauty vloggers, it can also be an easy way to ask trusted relatives about the various alternative products available. In this study, the population is executive member customers of Natasha Skin Care, as for data processing using SPSS 22 with the aim of determining the amount of influence of word of mouth in influencing the purchase decision of Natasha Skin Care products. The results showed that purchasing decisions were positively and significantly influenced by word of mouth by 42.2%. This shows that the increasing word of mouth will increase consumer purchasing decisions towards purchasing Natasha Skin Care products. Keywords: word of mouth, purchase decision